Islamic Education in the Abbasid Period: Development and Contribution to Islamic Civilization - Ratu Suntiah; Irfan Ahmad Zain; Erma Fitriya; Qorie Hizratul Muttaqien; Wisnu Hambali Hidayat; Imas Khotimah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the development of Islamic education during the Abbasid Dynasty, known as the Golden Age of Islam, and its role in shaping world civilization. This study focuses on the structure and methods of education, the contribution of institutions such as maktabs, madrasas, and Bait al-Hikmah, influential scholars, and their influence on society. This study uses a library research methodology. Data were collected through the analysis of primary sources, including the works of scientists in the Abbasid era, as well as secondary sources in the form of history books and studies related to the development of Islamic education. The results revealed that Islamic education during the Abbasid Dynasty experienced rapid development through the establishment of formal educational institutions, the application of innovative teaching methods such as the diploma system, as well as the contribution of renowned scientists such as Al-Kindi, Ibn Sina, and Al-Khwarizmi. These advancements led to major impacts, such as an increase in literacy levels, the integration of religious and secular sciences, and the transfer of knowledge to other civilizations, including Europe. This finding confirms the crucial role of the Abbasid Dynasty in building the foundation of Islamic intellectual civilization that is influential to this day.